2021
DOI: 10.1177/13591045211017617
|View full text |Cite
|
Sign up to set email alerts
|

Shared or unique trajectories of PTSD and depression in children over time since an earthquake

Abstract: Posttraumatic stress disorder (PTSD) and depression are common outcomes in children and adolescents following natural disasters. However, because of the comorbidity of PTSD and depression, their mutual relationship affects their relative trajectories over time. Therefore, this study examined the joint trajectories of PTSD and depression and assessed their consistency over time. Using self-report questionnaires, we surveyed 303 children in the worst-affected area of the Ya’an earthquake at 6 months, 1 year, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 67 publications
2
6
0
Order By: Relevance
“…While this observation conforms to previously identified developmental trajectories of PTSD and depressive symptoms in heterogeneous samples (Armenta et al, 2019; Eli et al, 2020; Oh et al, 2016; X. Zhou & Wu, 2021), there was no consistent pattern in the literature. Our current finding is consistent with some previous studies (Oh et al, 2016; Zhen et al, 2020), suggesting that PTSD and depressive symptoms are a general posttraumatic response rather than distinct disorders (Norman et al, 2011; Zhen et al, 2020).…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…While this observation conforms to previously identified developmental trajectories of PTSD and depressive symptoms in heterogeneous samples (Armenta et al, 2019; Eli et al, 2020; Oh et al, 2016; X. Zhou & Wu, 2021), there was no consistent pattern in the literature. Our current finding is consistent with some previous studies (Oh et al, 2016; Zhen et al, 2020), suggesting that PTSD and depressive symptoms are a general posttraumatic response rather than distinct disorders (Norman et al, 2011; Zhen et al, 2020).…”
Section: Discussionsupporting
confidence: 72%
“…The literature has repeatedly found that these two predictors are related to reduced PTSD and/or depressive symptoms (Armenta et al, 2019; Cénat et al, 2020; Demirchyan et al, 2022; Lai et al, 2015; X. Zhou & Wu, 2021). Individuals with high social support are more likely to gain purpose in life, self-esteem, and a sense of control or mastery of life, which help survivors build a more adaptive narrative of the traumatic event and thus alleviate psychological distress (X.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations